197k views
4 votes
Simplify z^6x^7/z^5x

2 Answers

4 votes

Answer:


zx^6 is the simplified answer.

Explanation:


(z^6x^7)/(z^5x)


\mathrm{Apply\:exponent\:rule}:\quad (x^a)/(x^b)=x^(a-b)\\\\=(x^7z^(6-5))/(x)\\\\=(zx^7)/(x)\\\\\mathrm{Cancel\:the\:common\:factor:}\:x\\\\=zx^6

Best Regards!

User Carry
by
4.8k points
3 votes

Answer:


\huge\boxed{(z^6x^7)/(z^5x)=zx^6}

Explanation:


\text{Use}\ (a^n)/(a^m)=a^(n-m)\\\\(z^6x^7)/(z^5x)=(z^6x^7)/(z^5x^1)=z^(6-5)x^(7-1)=z^1x^6=zx^6

User Antonpug
by
4.7k points